Pengaruh Work-Life Balance dan Dukungan Organisasi Terhadap Tingkat Burnout Pada Karyawan Dengan Sistem Kerja Hybrid di Kota Semarang - Serhemia Rahayu; Suparmi Suparmi; Tri Widayati; Amsar Amsar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The transformation of work systems in the post-pandemic era has encouraged organizations to adopt hybrid working arrangements that may influence employees’ psychological well-being. One of the most prominent consequences is the heightened risk of burnout resulting from an imbalance between professional responsibilities and personal life roles. This study aims to analyze the effect of work-life balance and organizational support on burnout levels among employees working under a hybrid work system in Semarang City. A quantitative approach with an explanatory research design was employed. The study involved 100 respondents determined using the Lemeshow formula and selected through purposive sampling techniques. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis. The findings indicate that work-life balance has a negative and statistically significant effect on burnout, indicating that better work-life balance is associated with lower levels of employee burnout. Organizational support also demonstrates a negative and significant influence on burnout. These results highlight the importance of work-life balance and organizational support in reducing employee burnout within hybrid work systems.